Sweet′s Syndrome Leading To Acquired Cutis Laxa (Marshall′s Syndrome) In A Child - Narayanan Meenakshi; Phiske Meghana; Jerajani H. R; Dhurat Rachita (Wolters Kluwer Medknow Publications, 2004)
Acute febrile neutrophilic dermatosis (AFND), commonly known as Sweetâ€s syndrome, is a disorder seen in adult females, being extremely rare in children. Typical features include spiky fever, sudden eruption of raised painful erythematous to plum-colored nodules and plaques, neutrophilic leucocytosis, a dermal neutrophili infiltrate an a rapid response to systemic steroid. The eruption is believed to represent a hypersensitivity reaction to an antecedent infection or malignancy. There have been rare reports of acquired cutis laxa (Marshallâ€s syndrome) following Sweetâ€s syndrome. We report one such case of Sweetâ€s syndrome leading to acquired cutis laxa (Marshallâ€ syndrome) in a child.